IDENTIFIKASI FAKTOR RESIKO YANG BERPERAN SEBAGAI SUMBER PENULARAN PENYAKIT AFRICAN SWINE FEVER DI KOTA DAN KABUPATEN KUPANG - Andrijanto Hauferson Angi; Defrys R. Tulle (Partner, 2022)
African swine fever (ASF) is a hemorrhagic infectious disease in pigs caused by a DNA virus from the Asfarviridae family of the genus Asfivirus. An effective vaccine against ASF has not yet been found. This study aims to identify factors that play a role as a source of transmission of ASF disease in pig farms in Kupang City and Regency. Analyze the data in a description with interviews with 60 pig breeders. Factors that are the source of transmission of the ASF virus include the origin of pig livestock from traditional farms (7,7%) and animal markets (6,7%), feed sources are garbage feed (61,7%), non-routine health checks (90%), dead pigs their carcasses are thrown into landfills (20%), waste is disposed of in sewers (33,3%). Another factor that plays a role is that breeders do not know Ornithodoros sp. as a carrier vector of the ASF virus as well as if the pig is sick the farmer immediately sells his pig (60 %). Key Word: ASF, Transmission, Kupang City and Regancy